Design of 4.48–5.89 GHz LC-VCO in 65 nm RF CMOS Technology - Macaitis, V.; Barzdenas, V.; Navickas, R. (Elektronika ir Elektrotechnika, 2014)
This paper describes a 4.48 GHz–5.89 GHz LC voltage-controlled oscillator (LC-VCO) as a key component in RF transceivers. The circuit is fully designed in TSMC’s 65 nm radio-frequency complimentary metal-oxide-semiconductor technology process. The LC-VCO uses the structure of only one couple of NMOS differential negative resistances, tank circuit which consists of an optimal on-chip spiral inductor with switched capacitor and varactor arrays. The proposed design accomplishes wide tuning range frequency by using 6-bit switch capacitor array in addition to linearly varying MOS varactors. A switched current source block is used to improve the performance of the LC-VCO. The oscillator has a wide tuning range, between 4.48 GHz and 5.89 GHz. The LC-VCO dissipates 15.96 mW from a voltage supply of 1.8 V, whereas its phase noise is -124.1 dBc/Hz at 1 MHz offset of a at 5.89 GHz carrier. DOI: http://dx.doi.org/10.5755/j01.eee.20.2.6383